n = 1 ∑ ∞ ( 3 n − 1 ) ! 8 n = B A e − C ( e D − E sin ( F π + G ) )
If A , B , C , D , E , F and G are positive integers satisfying the equation above, find min ( A + B + C + D + E + F + G ) .
Hint : Algebraic approach is easier than calculus approach.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Perfect one! Nice solution!
Hi Ariel, are you on Slack ? It's a social platform where most of the active users here (even the staffs) are there, and we talk about nothing except for math and science? Care to join us? It's free! Plus, there's a private channel where we discuss and share about difficult interesting series/integrals, you will definitely love it there!
Log in to reply
No, I'm not on Slack. Sure, sounds interesting!
I recently saw a solution to a similar problem, which gave me an idea for a better solution to this one:
n = 1 ∑ ∞ ( 3 n − 1 ) ! 2 3 n = k = 0 ∑ ∞ k ! 2 k + 1 ( 3 1 + 3 2 cos ( 3 2 π ( k + 1 ) ) ) = 3 2 k = 0 ∑ ∞ k ! 2 k + 3 4 k = 0 ∑ ∞ k ! 2 k R e [ e 3 2 π ( k + 1 ) i ] = 3 2 e 2 + R e ⎣ ⎢ ⎡ 3 4 e 3 2 π i k = 0 ∑ ∞ k ! ( 2 e 3 2 π i ) k ⎦ ⎥ ⎤ = 3 2 e 2 + R e [ 3 4 e 3 2 π i e − 1 + 3 i ] = 3 2 e 2 + R e [ 3 e 4 e ( 3 2 π + 3 ) i ] = 3 2 e 2 + 3 e 4 cos ( 3 2 π + 3 ) = 3 e 2 [ e 3 − 2 sin ( 6 π + 3 ) ]
This is way better than the previous one.
Problem Loading...
Note Loading...
Set Loading...
Replace 8 n with 2 3 n , and this looks like the Taylor series of x e x with only one-third of the terms. My strategy is to find a function f ( x ) whose Taylor series is ∑ n = 1 ∞ ( 3 n − 1 ) ! x 3 n
First, denote w = 2 − 1 + − 3 , so that w 2 = 2 − 1 − − 3 and w 3 = 1 . Since the terms are nonzero periodically with a period of 3, I am going to make an educated guess that f ( x ) has the form p x e w x + q x e w 2 x + r x e x . This function will have the following Taylor Series: k = 0 ∑ ∞ k ! ( p w k + q w 2 k + r ) x k + 1
Substituting k = 3 n , 3 n + 1 and 3 n − 1 gives us the following system of equations: p + q + r = 0 w p + w 2 q + r = 0 w 2 p + w q + r = 1 Solving this gives p = 3 w , q = 3 w 2 , r = 3 1 . Therefore, f ( x ) = 3 x ( w e w x + w 2 e w 2 x + e x )
Therefore, f ( 2 ) = n = 0 ∑ ∞ ( 3 n − 1 ) ! 2 3 n = 3 2 ( w e 2 w + w 2 e 2 w 2 + e 2 ) = 3 2 ( e 3 2 π e − 1 + 3 i + e 3 − 2 π e − 1 − 3 i + e 2 ) = 3 e 2 ( e ( 3 2 π + 3 ) i + e ( 3 − 2 π − 3 ) i + e 3 ) = 3 e 2 [ cos ( 3 2 π + 3 ) + i sin ( 3 2 π + 3 ) + cos ( 3 − 2 π − 3 ) + i sin ( 3 − 2 π − 3 ) + e 3 ] = 3 e 2 [ e 3 + 2 cos ( 3 2 π + 3 ) ] = 3 e 2 [ e 3 − 2 sin ( 6 π + 3 ) ]
Hence, the answer is 2 + 3 + 1 + 3 + 2 + 6 + 3 = 2 0 .